Influence of the use of learning strategies in the level of research skills in postgraduate students in dentistry - Alfaro-Carballido, Dahiana (2018)
Objetive: To determine if the use of learning strategies and motivation influence the level of research skills in postgraduate students in dentistry of the Universidad de San Martín de Porres. Materials and Methods: 130 students were surveyed with a non-response rate of 16.07% which belong to the programs of masters and specialities, which were randomly selected. We used two questionnaires 1) learning strategies and motivation and 2) questionnaire to evaluate the rsearch skills which was previously validated. Results: Descriptive analysis of the data, Chi2 and ANOVA was carried out to evaluate the association between the variables and the ratio of prevalence with the linear regression test of Poison. An association was found regarding the variables study time, previous scientific work, membership of a scientific association and antecedets of research and methods of study courses Chi2 (p<0.05), we also found association with motivation and learning strategies ANOVA (p<0.05) highlighting Internal motivation of the student and critical thinking in all stages of research (p<0.05). Conclusions: It was found that students who have a high level of use of learning strategies and motivation are almost three times more likely to have high research skills (RP: 2.82 CI = 1.55-5.14 ), Have a medium to high level of research skills (58%).